A Rhenium Isonitrile Complex Induces Unfolded Protein Response‐Mediated Apoptosis in Cancer Cells. Issue 39 (26th June 2019) - King, A. Paden; Marker, Sierra C.; Swanda, Robert V.; Woods, Joshua J.; Qian, Shu‐Bing; Wilson, Justin J.
Abstract: Complexes of the element Re have recently been shown to possess promising anticancer activity through mechanisms of action that are distinct from the conventional metal‐based drug cisplatin. In this study, we report our investigations on the anticancer activity of the complex [Re(CO)3 (dmphen)( p ‐tol‐ICN)] + (TRIP) in which dmphen=2, 9‐dimethyl‐1, 10‐phenanthroline and p ‐tol‐ICN= para ‐tolyl isonitrile. TRIP was synthesized by literature methods and exhaustively characterized. This compound exhibited potent in vitro anticancer activity in a wide variety of cell lines. Flow cytometry and immunostaining experiments indicated that TRIP induces intrinsic apoptosis. Comprehensive biological mechanistic studies demonstrated that this compound triggers the accumulation of misfolded proteins, which causes endoplasmic reticulum (ER) stress, the unfolded protein response, and apoptotic cell death. Furthermore, TRIP induced hyperphosphorylation of eIF2α, translation inhibition, mitochondrial fission, and expression of proapoptotic ATF4 and CHOP. These results establish TRIP as a promising anticancer agent based on its potent cytotoxic activity and ability to induce ER stress. Abstract : An anticancer rhenium complex : A newly synthesized rhenium tricarbonyl complex kills cancer cells by inducing the accumulation of unfolded proteins, leading to activation of the unfolded protein response and apoptosis.